Application of Cleaner technologies – case study - Kalmath, Manjunathswamy; kumar, Dr Sampath (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Cleaner technology is a preventive, company specific environmental production initiative. It is intended to minimize waste and emission and maximize product output. For the present research study an automobile parts manufacturing industry in Bangalore is chosen as study area”. The present study carried out on three major areas such as Environmental Management System practices (EMS), organic waste management (food waste) and application of statistical tools to automated effluent treatment plant. The food waste generated in Ban-P canteen area has been effectively utilized for converting organic waste into Biogas by designing 25M3 plants for 250 kg of food waste. The designed plant estimation gives out saving of 16 cylinders of 19 kg weight which accounts for 2.48,650 rupees and 250 tones of CO2e /annum will be reduced. The study on Environmental Management System practices in Bosch has been carried out with respect to Environmental Objectives, employee training, aspect/ impact registration, internal audit and etc. The standard statistical tools have been applied to AETP in-order to predict the effluent parameters such as BOD,COD,TDS,TSS etc., correlation analysis between all the effluent parameters has been studied, finally comparison between effluent parameters and standards has been assessed using one t test.